Analysis of Circulating MicroRNAs In Vivo following Administration of Dexamethasone and Adrenocorticotropin - Ivan Igaz; Gábor Nyírő; Zoltán Nagy; Henriett Butz; Zsolt Nagy; Pál Perge; Peter Sahin; Miklós Tóth; Károly Rácz; Peter Igaz; Attila Patócs (International Journal of Endocrinology)
Purpose. The interaction of hormones of the pituitary-adrenal axis and adrenal cortex-associated circulating microRNAs is mostly unknown. We have studied the effects of dexamethasone and adrenocorticotropin on the expression of five circulating microRNAs (hsa-miR-27a, hsa-miR-200b, hsa-miR-214, hsa-miR-483-5p, and hsa-miR-503) reported to be related to the adrenal cortex in plasma samples. Methods. Expression of microRNAs was studied in plasma samples of 10 individuals examined by 1 mg dexamethasone suppression test and another 10 individuals stimulated by 250 μg tetracosactide (adrenocorticotropin). Total RNA was isolated and microRNA expression was analyzed by real-time reverse transcription quantitative polymerase chain reaction normalized to cel-miR-39 as reference. Results. Only circulating hsa-miR-27a proved to be significantly modulated in vivo by hormonal treatments: its expression was upregulated by dexamethasone whereas it was suppressed by adrenocorticotropin. Secreted hsa-miR-27a was significantly induced by dexamethasone in vitro in NCI-H295R cells, as well. The expression of hsa-miR-483-5p proposed as diagnostic marker for adrenocortical malignancy was not affected by dexamethasone or tetracosactide administration. Conclusions. hsa-miR-27a expression is modulated by hormones of the hypothalamic-pituitary-adrenal axis both in vitro and in vivo. The biological relevance of hsa-miR-27a modulation by hormones is unclear, but the responsiveness of circulating microRNAs to hormones of the pituitary-adrenal axis is noteworthy.